AB0128 Expression of aberrantly glycosylated mucins (tn and sialyl tn antigens) and muc1 in labial salivary gland of patients with sjogren's syndrome. (23rd January 2014) - Ishino, H.; Kohno, M.; Kajitani, N.; Yamamoto, A.; Seno, T.; Murakami, K.; Fujii, W.; Nagahara, H.; Nakada, H.; Kawahito, Y.
Abstract : Background: Primary Sjogren syndrome (SS) is an autoimmune exocrinopathy. Mucin are present on apical surfaces of all healthy wet surface epithelia of human body and on the glands of simple secretory epithelial tissue. The major and minor salivary glands express the membrane-bound mucin, MUC1. Tn and sialyl-Tn antigens are tumor-associated carbohydrate antigens expressed on mucins in epithelial cancers. Alteration of glycoproteins is related with various immunoreactions. The study of sugar chains in autoimmune diseases is intriguing, however, there have been few reports on abnormalities of sugar chains, especially in the pathogenesis of SS. The functions of Tn and sialyl-Tn antigens, MUC1 expressed in human salivary gland is unknown. Objectives: The carbohydrate chains represented by mucins are expressed by a variety of normal and malignant secretory epithelial cells and induce a variety of immunoreactions. The purpose of this study is to investigate the existence and bioactivity of tumor-associated carbohydrate antigens in SS. Methods: A total of eleven patients (females) with primary SS (mean (SD) age = 52.4 (13.5) years) were enrolled. Saliva was collected by the gum test. Labial salivary gland biopsies were obtained in 11 patients. We examined the expression of Tn, sialyl Tn antigens, and MUC1 in salivary glands tissues from SS patients by immunohistochemistry. In addition, saliva from SS patients was subjected to gel filtration on Sepharose 6B and collected the fractions including mucins. The tumor necrosis factor (TNF)-α and prostaglandin E2 (PGE2 ) production by mucin in human peripheral blood monocytes (PBMC) were also investigated using ELISA. Results: We found that Tn and sialyl Tn antigens, MUC-1 were strongly expressed in mucous acinar cells and infiltrating mononuclear cells on the labial salivary gland (p<0.001) (Image A). Western blotting and a dot blot analysis revealed that saliva fractions include these mucins. Saliva fractions can stimulate the production of TNF-α (Image B) and PGE2 (Image C) in human PBMC. Image/graph: Conclusions: We revealed that Tn and sialyl Tn antigens typical malignancy-associated mucins, MUC-1 expressed in SS salivary glands. We found an aberrantly glycosylated mucin from saliva in patients with SS, which can produce TNF-α and PGE2 in human PBMC. This finding suggests that the mucins exhibiting with abnormal glycosylation may be in part responsible for salivary glands inflammation, leading to the salivary glands destruction in the pathogenesis of SS. References: Reduced sulfation of muc5b is linked to xerostomia in patients with Sjögren syndrome. Alliende C, et, al. Ann Rheum Dis. 2008 Oct;67(10):1480-7. Expression of Tn and sialyl Tn antigens in synovial tissues in rheumatoid arthritis. Ishino H, et, al. Clin Exp Rheumatol. 2010 Mar-Apr;28(2):246-9. Disclosure of Interest: H. Ishino Grant/research support from: Grants-in-Aid for Scientific Research, M. Kohno: None Declared, N. Kajitani: None Declared, A. Yamamoto: None Declared, T. Seno: None Declared, K. Murakami: None Declared, W. Fujii: None Declared, H. Nagahara: None Declared, H. Nakada: None Declared, Y. Kawahito: None Declared